Usage of Hemopoietic Precursor Cells for Correcting Immune-Physiological Disorders Under Dangerous and Critical States - Klimova, E. M.; Drozdova, L. A.; Shakina, L. A.; Antonenko, T. S.; Merezhko, O. S. (Problems of Cryobiology and Cryomedicine, 2008)
This research shows the usage of hemopoietic stem cells (HSCs) of fetal liver and cord blood hemopoietic precursor cells (CB HPCs) for correcting immunological disorders in patients with hepatocirrhosis, pancreas necrosis, diabetes of II type, Larish syndrome, polytrauma. The disorders in cell and humoral links of immune response have been revealed in the examined patients at their entering in the hospital. The HSCs and CB HPCs transfusions in the most of patients resulted in the positive changes of circulating immune complexes (CICs) concentration, CICs constant values, lymphotoxicity, level of CD3+, CD4+, CD8+ differentiated markers.